Ca. 1.5 Ga mafic magmatism in South China during the break-up of the supercontinent Nuna/Columbia: The Zhuqing Fe–Ti–V oxide ore-bearing mafic intrusions in western Yangtze Block - Fan, H.; Zhu, W.; Li, Zheng-Xiang; Zhong, H.; Bai, Z.; He, D.; Chen, C.; Cao, C. (Elsevier BV, 2013)
Secondary ion mass spectroscopy (SIMS) zircon and baddeleyite U–Pb ages, elemental, and Nd isotopic data are reported for the Zhuqing Fe–Ti–V oxide ore-bearing mafic intrusions in western Yangtze Block, South China. The mafic intrusions are dated at 1494±6 Ma (zircon U–Pb), 1486±3 Ma (baddeleyite U–Pb) and 1490±4 Ma (baddeleyite U–Pb). The intrusions are dominantly gabbros that experienced variable degrees of alteration. All the studied rocks are high-Ti and alkaline in composition, and exhibit light rare earth element enrichment and “humped” incompatible trace-element patterns with no obvious Nb–Ta depletion, similar to intraplate alkali basaltic rocks in continental flood basalt (CFB) and ocean island basalt (OIB) provinces. Negative εNd(T)values (-0.97 to -3.58) and fractionation of the HREE of these rocks indicate that they were derived from a time-integrated, slightly enriched asthenospheric mantle source with minor crustal contamination. Like other Fe–Ti oxide mineralized rocks in plume-related layered intrusions or large igneous provinces around the world, the Zhuqing gabbros likely occurred in an intraplate setting. The ~1.5 Ga mafic magmatism was likely part of the global 1.6–1.2 Ga anorogenic magmatism related to the break-up of the supercontinent Nuna/Columbia, suggesting that the Yangtze Block may have been a component of the supercontinent.